2017
DOI: 10.1104/pp.16.01302
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biosensors for in Vivo Spatiotemporal Mapping of Root Secretion

Abstract: Plants engineer the rhizosphere to their advantage by secreting various nutrients and secondary metabolites. Coupling transcriptomic and metabolomic analyses of the pea (Pisum sativum) rhizosphere, a suite of bioreporters has been developed in Rhizobium leguminosarum bv viciae strain 3841, and these detect metabolites secreted by roots in space and time. Fourteen bacterial lux fusion bioreporters, specific for sugars, polyols, amino acids, organic acids, or flavonoids, have been validated in vitro and in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(119 citation statements)
references
References 45 publications
5
108
0
Order By: Relevance
“…This is consistent with a previous study on root exudates under similar conditions [92]. Previous studies reported that the amounts of secreted avonoids increased by inoculation with compatible symbionts or by treatment with Nod factors and were reduced by inoculation with nodC mutant rhizobium [35,36,93]. Accordingly, we found a signi cantly increased exudation of most avonoids when inoculating the WT strain.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with a previous study on root exudates under similar conditions [92]. Previous studies reported that the amounts of secreted avonoids increased by inoculation with compatible symbionts or by treatment with Nod factors and were reduced by inoculation with nodC mutant rhizobium [35,36,93]. Accordingly, we found a signi cantly increased exudation of most avonoids when inoculating the WT strain.…”
Section: Discussionsupporting
confidence: 93%
“…Recent work has suggested that culturing rhizobia in the latter is correlated with an increase in mutations of symbiosis-associated genes 50 , raising questions about the utility of rich medium cultures in symbiosis work overall. A more detailed analysis of the host environment, including the full milieu of root exudates 51 , available carbon sources 52 and trace metals specific to each legume, will improve in vitro models of legume-bacteria interactions.…”
Section: Discussionmentioning
confidence: 99%
“…viciae 3841 data contains gene expression information observed under 18 different growth conditions. These data come from n = 54 microarray channels with 3 independent samples per condition (Ramachandran et al, 2011;Pini et al, 2017;Karunakaran et al, 2009). The complete list of the conditions is in Sec.…”
Section: Datamentioning
confidence: 99%